Transcending technology boundaries and maintaining sense of community in virtual mental health peer support: a qualitative study with service providers and users - Elmira Mirbahaeddin; Samia Chreim (BMC, 2024)
Abstract Background This qualitative study explores the experiences of peer support workers (PSWs) and service users (or peers) during transition from in-person to virtual mental health services. During and following the COVID-19 pandemic, the need for accessible and community-based mental health support has become increasingly important. This research aims to understand how technological factors act as bridges and boundaries to mental health peer support services. In addition, the study explores whether and how a sense of community can be built or maintained among PSWs and peers in a virtual space when connections are mediated by technology. This research fills a gap in the literature by incorporating the perspectives of service users and underscores the potential of virtual peer support beyond pandemic conditions. Methods Data collection was conducted from a community organization that offers mental health peer support services. Semi-structured interviews were conducted with 13 employees and 27 service users. Thematic analysis was employed to identify key themes and synthesize a comprehensive understanding. Results The findings highlight the mental health peer support needs that were met through virtual services, the manifestation of technology-based boundaries and the steps taken to remove some of these boundaries, and the strategies employed by the organization and its members to establish and maintain a sense of community in a virtual environment marked by physical distancing and technology-mediated interrelations. The findings also reveal the importance of providing hybrid services consisting of a mixture of in person and virtual mental health support to reach a broad spectrum of service users. Conclusions The study contributes to the ongoing efforts to enhance community mental health services and support in the virtual realm. It shows the importance of virtual peer support in situations where in-person support is not accessible. A hybrid model combining virtual and in-person mental health support services is recommended for better accessibility to mental health support services. Moreover, the importance of organizational support and of equitable resource allocation to overcome service boundaries are discussed.